The Effect of Project-Based Learning Integrated with Window-Shopping Strategy on EFL Students' Speaking Skills, Motivation, and Anxiety: A Quasi-Experimental Study - Edi Suyanto; Annur Rofiq; David Imamyartha; Budi Setyono; Siti Masrifatul Fitriyah (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2026)
English speaking ability is an important skill in a global context, but it remains a major challenge for EFL students due to low motivation and high levels of communication anxiety. Therefore, innovative learning strategies are needed to address these issues. This study aims to analyze the effect of project-based learning integrated with window-shopping strategies on EFL students' speaking skills, motivation, and anxiety. This study used a quantitative approach with a quasi-experimental design in the form of a pre-test–post-test control group design involving 60 students as samples, who were divided into an experimental group and a control group. Data analysis techniques used instrument validity and reliability tests, normality and homogeneity tests, and hypothesis testing through paired sample t-tests and independent sample t-tests with the help of SPSS. The results showed that there was a significant increase in speaking skills (Sig. = 0.000), an increase in learning motivation (Sig. = 0.000), and a decrease in anxiety (Sig. = 0.000) in the experimental group compared to the control group, so that all research hypotheses were accepted. Thus, it can be concluded that the integration of Project-Based Learning and window-shopping strategies is effective in improving EFL students' speaking and affective skills. This research contributes to the development of innovative interaction- and collaboration-based learning models and has practical implications for teachers in creating more communicative and student-centered learning.